Analisis Perencanaan Partisipatif terhadap Pencapaian Kinerja Pegawai pada Kantor Sekretariat DPRD Kota Gunungsitoli - Eduar Baene (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2019)
Planning is the process of defining organizational goals, making strategies to achieve that goal, and developing plans for organizational work activities. While performance is what is done and what is not done by employees is the work that has been achieved by employees. The purpose of this study was to determine the effect of participatory planning on employee performance at the Secretariat of the Regional Representatives Office of the Gunungsitoli City. In this study the authors analyzed the research data using quantitative methods. The dependent variable (Y) of this study is performance, while the independent variable (X) is planning. The population in this study were all employees in the Secretariat Office of Gunungsitoli City DPRD, while the sample was 24 people. Based on the data collected from the research conducted, the results were obtained that there was an influence of participatory planning on employee performance at the Gunungsitoli City DPRD Secretariat Office